Multiple Nodal Solutions for Some Fourth-Order Boundary Value Problems via Admissible Invariant Sets. (9th October 2008) - Yang, Yang; Zhang, Jihui; Zhang, Zhitao
Abstract : Existence and multiplicity results for nodal solutions are obtained for the fourth-order boundary value problem (BVP)u ( 4 ) ( t ) = f ( t, u ( t ) ), 0 < t < 1, u ( 0 ) = u ( 1 ) = u ′ ′ ( 0 ) = u ′ ′ ( 1 ) = 0, wheref : [ 0, 1 ] × R → R is continuous. The critical point theory and admissible invariant sets are employed to discuss this problem.